Evaluation of in silico toxicity of monoterpene ascaridol (Research, Society and Development, 2020)
The aim of the present work is to evaluate the in silico toxicity of the monoterpene ascaridol. In the evaluation of toxicity, an in silico study was performed using the AdmetSAR tool to determine AMES Mutagenic Potential, Acute Oral Toxicity (TOA), Carcinogenic Potential (CP) and Carcinogenicity (Car). After the analysis of the substance it was observed that it did not present mutagenic potential by the AMES test, revealing low carcinogenic potential and had a TOA with category II, which showed LD50 ranging from 50mg\Kg - 500mg\Kg. The results demonstrate that ascaridol is absent in mutagenic, carcinogenic and moderate TOA potentials, such characteristics that make this substance viable for future in vitro and in vivo analyzes seeking better use of its bioactive potential in therapeutic targets.